Stress corrosion cracking behavior and mechanism of super 13Cr stainless steel in simulated O2/CO2 containing 3.5 wt% NaCl solution. (December 2021) - Luo, Sheji; Fu, Anqing; Liu, Ming; Xue, Yuna; Lv, Naixin; Han, Yan
Highlights: Stress corrosion cracking (SCC) tests were employed. Super 13Cr stainless steel is sensitive to SCC in O2 /CO2 /Cl - containing environment. O2 can aggravate the corrosion process in CO2 containing environment. Applied polarization potentials play an important role in the process of SCC. Abstract: Good CO2 corrosion resistance has made super 13Cr martensitic stainless steel become widely used in oil industry. However, the corrosion of OCTG (Oil CountryTubular Goods) changes from pure CO2 to O2 /CO2 /Cl - and other multi-component containing complex environment. To clarify the stress corrosion cracking (SCC) behavior and fracture mechanism of the super 13Cr stainless steel in the corrosive environment containing O2, CO2 and Cl -, the effect of applied potential on the SCC susceptibility of super 13Cr stainless steel in a 10% O2 and 90% CO2 containing 3.5 wt% NaCl solution was investigated by means of potentiodynamic polarization, slow strain rate tensile (SSRT) test and combined with scanning electron microscopy (SEM). The results show that the polarization potential has an influence on the SCC susceptibility of super 13Cr stainless steel in O2 /CO2 /Cl - containing medium. The SCC susceptibility is high with the anode and cathode polarization applied, and increases with the rise of the absolute potential values. The SCC mechanism has the following relationships with the applied potentials: a) anodic dissolution happens at 50 mV and 250 mV, b) anodic dissolution and hydrogen embrittlement were observed at −300 mV, and c) hydrogen embrittlement was obtained at −800 mV and −1000 mV.